2009
DOI: 10.1074/jbc.m109.055665
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of 4-Hydroxyacids and 4-Hydroxynonenal via 4-Hydroxy-4-phosphoacyl-CoAs

Abstract: 4-Hydroxyacids are products of ubiquitously occurring lipid peroxidation (C 9 , C 6 ) or drugs of abuse (C 4 , C 5 ). We investigated the catabolism of these compounds using a combination of metabolomics and mass isotopomer analysis. Livers were perfused with various concentrations of unlabeled and labeled saturated 4-hydroxyacids (C 4 to C 11 ) or 4-hydroxynonenal. All the compounds tested form a new class of acyl-CoA esters, 4-hydroxy-4-phosphoacyl-CoAs, characterized by liquid chromatography-tandem mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(104 citation statements)
references
References 48 publications
(80 reference statements)
8
95
1
Order By: Relevance
“…Although challenges of profi ling acyl-CoAs exist, common fragmentation patterns of acyl-CoAs in LC-MS/MS were found by us and others ( 4,6,23,24 ), and these common fragmentation patterns enable broad profi ling. In this work, a novel MRM method was developed to quantitatively scan acyl-CoAs in different rat organs according to the characteristic fragmentation pattern of acyl-CoAs in MS/MS.…”
Section: Lc-ms/ms Is the Most Sensitive Methods To Analyze Acylcoas Anmentioning
confidence: 70%
“…Although challenges of profi ling acyl-CoAs exist, common fragmentation patterns of acyl-CoAs in LC-MS/MS were found by us and others ( 4,6,23,24 ), and these common fragmentation patterns enable broad profi ling. In this work, a novel MRM method was developed to quantitatively scan acyl-CoAs in different rat organs according to the characteristic fragmentation pattern of acyl-CoAs in MS/MS.…”
Section: Lc-ms/ms Is the Most Sensitive Methods To Analyze Acylcoas Anmentioning
confidence: 70%
“…21,22 Plasma samples were assayed for the mass distribution of glucose as previously reported. [23][24][25] Correction of measured mass isotopomer distributions for natural enrichment was performed using the CORMAT software.…”
Section: Gc-ms/lc-ms Analysismentioning
confidence: 99%
“…The concentrations and mass isotopomer distributions of acylCoA esters were assayed as in Ref. 5. The chromatographic conditions optimize the separation of short-and mediumchain acyl-CoAs.…”
Section: Methodsmentioning
confidence: 99%
“…Our interest in levulinate arose from our recent study of the metabolism of 4-hydroxyacids, which are products of lipid peroxidation (C 9 , C 6 ) or drugs of abuse (C 4 , C 5 ) (5,6). We showed that 4-hydroxyacids with 5 or more carbons are metabolized by two new pathways.…”
mentioning
confidence: 99%